Exophthalmos due to sterile neutrophilic dermatosis in a dog. (14th March 2017) - Sharpe, Emily K.; Meekins, Jessica M.; Bagladi‐Swanson, Mary; Rankin, Amy J.
Abstract: An 8‐year‐old castrated male Bichon Frise was presented to the Kansas State University Veterinary Health Center for evaluation of unilateral right‐sided exophthalmos, suspected secondary to a retrobulbar abscess. The dog had acutely developed right‐sided periorbital swelling, exophthalmos with pain on retropulsion, as well as multiple cutaneous exudative plaques on the feet and tail base. On ophthalmic examination, the dog also exhibited mild left‐sided exophthalmos with decreased, nonpainful retropulsion. Orbital ultrasound and CT were performed to evaluate the extent of bilateral orbital disease. Incisional biopsies were obtained from the affected right periorbital tissues and skin of the feet, and histopathology revealed severe neutrophilic inflammation of the dermis with no organisms detected. Histologic changes were consistent with sterile neutrophilic dermatosis. The dog achieved clinical remission following treatment with initial immunosuppressive doses of corticosteroids and subsequent long‐term maintenance therapy using oral cyclosporine.